Security Methods to Improve Quality of Service - Agarwal, Nidhi; Anjali; Chauhan, Anuj Singh; Kumar, Ankit (EAI Endorsed Transactions on Internet of Things, 2023)
INTRODUCTION: Security and Quality of Service (QoS) are two of the most critical aspects of communication networks. Security measures are implemented to protect the network from unauthorized access and malicious attacks, whereas QoS measures are implemented to ensure that the network is reliable, efficient, and can meet the demands of users. OBJECTIVES: This paper examines various methods of network security and their impact on the quality of service (QoS) in computer networks. The study analyses different types of network attacks, such as denial of service (DoS), distributed denial of service (DDoS), and intrusion attempts, and their impact on QoS. The paper also explores various security mechanisms, such as intrusion detection and prevention systems (IDPS), firewalls, virtual private networks (VPNs), and techniques for encryption, that can help mitigate network security threats while maintaining QoS.METHODS: The study evaluates the strengths and weaknesses of the security mechanisms in terms of their ability to provide protection against network attacks while minimizing the impact on QoS. RESULTS: The paper provides recommendations for organizations to enhance their network security posture while improving the QoS, such as implementing robust network security policies, investing in advanced security tools, and training employees to recognize and respond to network security incidents. CONCLUSION: This paper offers a comprehensive analysis of network security methods and their impact on QoS, providing insights and recommendations for organizations to improve their network security posture and maintain a high level of QoS.hese are the conclusions of this paper.